The Temporal Associations of B-Mode and Power-Doppler Ultrasonography, and Ovarian Steroid Changes of the Periovulatory Follicle and Corpus Luteum During Luteogenesis and Luteolysis in Jennies - Magalhaes, Humberto B. [UNESP]; Canisso, Igor F. [UNESP]; Dell-Aqua, Jose A. [UNESP] (Elsevier, 2023)
This study aimed to determine the associations between B-mode and Power-doppler ultrasonography and ovarian steroids of the periovulatory follicle and respective corpus luteum (CL) during luteogenesis and luteolysis in jennies. Twenty-four periovulatory follicles/estrus of correspondent one inter-ovulatory interval (n = 12 jennies) were assessed in the study. B-mode ultrasonography and teasing were carried out once day until the detection of a periovulatory follicle (≥28 mm, uterine edema, and signs of estrus). Thereafter, jennies were monitored at 4-hour-intervals by B-mode and Power-doppler ultrasonography. Closer to ovulation, jennies were hourly checked. Each CL was checked daily from luteogenesis to luteolysis. Plasma concentrations of estradiol and progesterone were assessed daily with chemiluminescence immunoassay. Granulosa echogenicity and thickness increased from -36 hour to -1 hour before ovulation in 70% of follicles (P < .05) and were strongly associated with impending ovulation (r = 0.80 and r = 0.70, respectively). The follicular-wall blood flow increased from -72 to -24 hour pre-ovulation, while the estradiol concentration declined from 42 pg/mL by -72 hour to 31.6 pg/mL by 24 hour before ovulation (P < .05). The vascularization of the periovulatory follicle decreased from 62% (-36 hour) to 37% (-1 hour) before ovulation (P < .05). The CL vascularization and progesterone concentration gradually increased, reaching the peak at 11- and 10-day after the ovulation, respectively (P < .05). The CL vascularization started to decline 3 day before luteolysis, while progesterone concentrations started to drop 4 day before luteolysis (P < .05). In conclusion, the structural changes of the periovulatory follicle detected on B-mode and Power-doppler can be used to detect impending ovulation in donkeys; however, Power-doppler, but not B-mode ultrasonography, can be used to assess CL function in jennies.
Keywords: Luteogenesis; Luteolysis; Periovulatory period; Steroid